Da’wah: transformation method in the new millenium and its challenges in forming an islamic community / Zanirah Mustafa@Busu, Badriah Nordin and Norazmila Yusuf. - Mustafa@Busu, Zanirah; Nordin, Badriah; Yusuf, Norazmila (2018)
Da'wah is a preaching to all mankind to return to Allah with great wisdom and to remind them of leaving the darkness of ignorance to the light of Islam until they believe in only Allah and leave behind the thaghut. The main purpose of preaching is ta'zim li amrillah which is to glorify the command of Allah and syafaqah 'ala ibadillah which is mercy or kindness to the servant of Allah. The da'wah approach used by the preachers is based on the target audience. It is clear to us that the movement of da'wah to the public is carried out in various forms, such as through places of worship like mosques and praying rooms, through educational places like educational institutions, religious educational huts (pondok) and so on. Furthermore, the content is also familiarized with Islamic culture in terms of clothing, social intercourse, hygiene and entertainment. We are also accustomed to Islam in family and neighborhood relationships and cultivating the spirit of brotherhood. Today, da'wah is facing various challenges and rejections. Duties and responsibilities of the preachers are increasingly demanding and challenging. Hence, this writing is intended to share knowledge, views and experiences on several methods and strategies of da'wah in order to facilitate current Islamic preachers. In addition, this paper also focuses on several processes of changes and transformation from a negative view to the enlightenment of identity which leads to the formation of an Islamic community. It demands the preachers to escape the scope of sentiment, emotion, public speaking and writing to the scope of planning, organizing, programming, preparing and building proposals and charities. The scope of da'wah has gotten wider with plenty of experiences and a wide range of communication approaches (uslub). The need for da’wah and its demands are extremely crucial. Such endeavor is necessary to restore the glory of Islam as in the days of the Prophet Rasulullah SAW and his Companions so that it remains relevant and has the ability to handle the spirit of da'wah with all the people in Malaysia.